Cooperative management reshapes seasonal nitrogen synchrony and surface-water nitrogen risk in pastoral regions - Tianyun Qi; Tianer Song; Mei Huang; Wenyin Wang; Binyu Luo; Shuai Qi; Cai’e Wang; Rong Rong; Lin Ma; Jianhui Xu; Tao Zhang; Yanfu Bai; et al. (Agriculture, Ecosystems & Environment, 2027)

A novel fungus Penicillium crocicola LF-2022 for high-efficiency biodegradation of brominated flame retardants: Performance, pathways, soil remediation, and transcriptomic mechanisms - Yan Li; Ruiying Wu; Zhenglin Xia; Zhinan Jiang; Haitao Wu; Chen Lin; Jiaqing Chen; Fei Li (Journal of Hazardous Materials, 2026)

Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Spontaneous plastome mutations in variegated plants occur predominantly in genes related to transcription and photosynthesis - Zhuoqiao Qiu; Boya Yi; Huajing Feng; Qi Zeng; Peishan Zou; Xirong Zheng; Jianzhong Ni; Manmei He; Ruiying Wang; Shuaixi Zhou; Kainan Ma; Shiou Yih Lee; et al. (Planta, 2026)

Litter inputs reshape soil respiration partitioning in subalpine forests: Pivotal role of microbial gene abundance and root-microbe interactions - Yuxiao Kuang; Jia Xiong; Linhui Zhang; Genxu Wang; Zhaoyong Hu; Wenzhi Wang; Juying Sun; Ruiying Chang; Xiangyang Sun; Yuanyuan Su; Shan Lin; Hailong Sun; et al. (Agricultural and Forest Meteorology, 2026)

Cryo-EM structures of Arabidopsis heteromultimeric isoamylase complex essential for starch granule biogenesis - Ruiying Wang; Wenjuan Li; Yutong Wu; Huajian Lin; Xiang Lin; Lizhi Zhu; Ruiqiang Ye; Jinru Zhang; Minrui Fan (Molecular Plant, 2026)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Optimization and characterization of dummy-template molecularly imprinted polymers as sorbents for the selective recognition of the polychlorinated biphenyls - Rui Wang; Lin Liang; Wenqin Yin; Ruiying Huang; Guanhui Li; Zexiang Lu; Liwei Fan (Environmental Research, 2025)

Estimation of Strain-Softening Parameters of Marine Clay Using the Initial T-Bar Penetration Test - Qinglai Fan; Zhaoxia Lin; Mengmeng Sun; Yunrui Han; Ruiying Yin (Journal of Marine Science and Engineering, 2025)
T-bar penetrometers have been widely used to measure strength parameters of marine clay in laboratory and in situ tests. However, using the deep resistance factor derived from full-flow conditions to evaluate the undrained shear strength of shallow clay layers may lead to significant underestimation. Furthermore, the deep resistance factor is inherently influenced by the strain-softening behavior of clay rather than maintaining the constant value (typically 10.5) as conventionally assumed in practice. To address this issue, large-deformation finite element (LDFE) simulations incorporating an advanced exponential strain-softening constitutive model were performed to replicate the full T-bar penetration process—from shallow embedment to deeper depths below the mudline. A series of parametric studies were conducted to examine the influence of key parameters on the resistance factor and the associated failure mechanisms during penetration. Based on numerical results, empirical formulas were derived to predict critical penetration depths for both trapped cavity formation and full-flow mechanism initiation. For penetration depths shallower than the full-flow depth, an expression for the softening correction factor was developed to calibrate the shallow resistance factor. Finally, combined with global optimization algorithms, a computer-aided back-analysis procedure was established to estimate strain-softening parameters using resistance-penetration curves from initial penetration tests in marine clay. The reliability of the back-analysis procedure was validated through extensive comparisons with a series of numerical simulation results. This procedure can be applied to the interpretation of T-bar in situ test results in soft marine clay, enabling the evaluation of its strain-softening behavior.

Nasopharyngeal cancer screening and immunotherapy efficacy evaluation based on plasma separation combined with label-free SERS technology - Ruiying Lin; Zhangying Jiang; Jinyong Lin; Feifei Tong; Yangmin Wu; Jinquan Hong; Sufang Qiu; Qiong Wu (Analytica Chimica Acta, 2025)

Understanding the deactivation factors for pre-classification of spent SCR catalysts treatment - Qiuyun Huang; Ruiying Hu; Zhen Wu; Xueming Liu; Qingwei Wang; Hao Chen; Fenghua Shen; Wenchao Zhang; Zhang Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Element Redistribution and Age Resetting in Shock-Deformed Zircon from the Chicxulub Impact Structure - Jiawei Zhao; Long Xiao; Zhiyong Xiao; Xiang Wu; Qi He; Jialong Hao; Ruiying Li; Yangting Lin (Geochimica et Cosmochimica Acta, 2025)

Mediating morphology evolution via the regulation of molecular interactions between volatile solid additives and electron acceptor to enable organic solar cells with 19.20% efficiency - Ruiying Lin; Zhenyu Luo; Yunfei Wang; Jiaxin Wu; Tao Jia; Wei Zhang; Xiaodan Gu; Yi Liu; Liangang Xiao; Yonggang Min (Chemical Engineering Journal, 2025)

Extremely large Cl isotopic fractionation in Chang'e-5 impact glass beads - Yue Zhang; Hejiu Hui; Sen Hu; Jialong Hao; Ruiying Li; Wei Yang; Qiuli Li; Yangting Lin; Xianhua Li; Fuyuan Wu (Earth and Planetary Science Letters, 2024)

Assessing the impacts of technological change on food security and climate change mitigation in China’s agriculture and land-use sectors - Xiaoxi Wang; Ruiying Du; Hao Cai; Bin Lin; Jan Philipp Dietrich; Miodrag Stevanović; Hermann Lotze-Campen; Alexander Popp (Environmental Impact Assessment Review, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Combination effects of ultrasound and citral nanoemulsion against Shigella flexneri and the preservation effect on fresh-cut carrots - Luyi Song; Hui Yang; Shuai Cheng; Zhen Zhang; Lechi Zhang; Ruiying Su; Yuxi Li; Xiangjun Zhan; Baowei Yang; Lin Lin; Chao Shi (Food Control, 2024)

Adding the third component with similar building blocks to regulate the miscibility of active layer enables high efficient ternary solar cells - Shichu Peng; Jinxin Luo; Peng Li; Liangang Xiao; Chongqing Yang; Yaocheng Jin; Ruiying Lin; Yanping Huo; Yi Liu; Yonggang Min (Chemical Engineering Journal, 2023)

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

Transcriptomics analysis reveals key lncRNAs and genes related to the infection of feline kidney cell line by panleukopenia virus - Lingling Zhang; Ruiying Liang; Abdul Raheem; Lin Liang; Xinglin Zhang; Shangjin Cui (Research in Veterinary Science, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Development of a TaqMan loop-mediated isothermal amplification assay for the rapid detection of pigeon paramyxovirus type 1 - Ruiying Liang; Lin Liang; Xiaoxia Ren; Yaxiong Jia; Kun Han; Jingjie Zhao; Cuiping Song; Shangjin Cui (Archives of Virology, 2021)

Moisture Adsorption Isotherms and Thermodynamic Properties of Penaeus vannamei Meat with and without Maltodextrin Addition - Qilong Shi; Wenwen Lin; Ya Zhao; Pingping Zhang; Ruiying Wang (Journal of Aquatic Food Product Technology, 2016)

WNT10A variants are associated with non-syndromic tooth agenesis in the general population - Shujuan Song; Ruiying Zhao; Huiying He; Jin Zhang; Hailan Feng; Liyun Lin (Human Genetics, 2014)